EFFECT OF DIFFERENT TYPES OF ORGANIC FERTILIZER IN VEGETATIVE GROWTH OF CACATS ( ALOE VERA L.) - & Rabee, Muneer (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was carried out on the Cactus (Aloe vera L.), two year old plants were planted in one of the fields of Agriculture College - Baghdad University for the season 2015-2016 and planted in pots. The different organic fertilizers used in two (Sewage, poultry manure and sheep manure) and the fertilize used at two levels 7.5% and 5% from the weight of the pot, and organic acid (Com Sol ) at two levels (1.5 and 3) ml and chemical fertilizer NPK (2.5 gm) in addition to control treatment. The experiment carried out within the RCBD with three replicates and four plants for each experimental unit. results were indicated that the sewage treatment at 7.5% caused significantly increased in rates of vegetative characteristics: leaves number (17.43 leaves per plant), offset number (10.57 offset per plant), plant height and width leaf (64.79 and 7.85) cm respectively, thickness leaf (2.24 mm), gel and cortex dry weight (9.96 and 27.21) gm respectively, and amount of chlorophyll (1.948 mg.gm-1 fresh weight) compared to the control treatment.